E shaped antennas (ESA) - (:unkn) unknown (My University, 2002)
Thin wire antennas is basic of the antenna theory. In the analysis, this antenna is considered as infinite thin, symmetric to feeding point, fed from center and has a direct-line geometry. Near filed of this antenna is determined by sinusoidal current distribution. Then some reduction is done. But especially physical condition required to change antenna geometry, for example reflector application. One of thin wire antenna geometry is E-shape. In this paper E shape antenna’s electrical field equation will be determined.
Keywords: Radiation impedance; Radiation pattern; Thin antennas